2021
DOI: 10.3341/kjo.2020.0143
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of Optical Coherence Tomography Angiography Measurements in Patients with Retinal Vein Occlusion

Abstract: Purpose To analyze the repeatability of vessel density (VD) measurements and manual foveal avascular zone (FAZ) measurements using optical coherence tomography angiography (OCTA) in patients with retinal vein occlusion (RVO) without macular edema. Methods The study population consisted of patients with RVO and central macular thickness <300 μm. For each subject, measurements were performed twice with a 5-minute interval. The intraclass correlation coefficient (ICC) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In addition, they highlighted that the image quality affects the repeatability of the VD measurement. In contrast, manual measurement of FAZ was highly reproducible in both SCP and DCP layers [ 89 ]. Rabiolo et al investigated several OCT-A system angiocubes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they highlighted that the image quality affects the repeatability of the VD measurement. In contrast, manual measurement of FAZ was highly reproducible in both SCP and DCP layers [ 89 ]. Rabiolo et al investigated several OCT-A system angiocubes.…”
Section: Resultsmentioning
confidence: 99%
“…FAZ borders can be selected manually (plot all vascular endpoints) and automatically. While the manual segmentation of FAZ has demonstrated its reliability in producing consistent outcomes [ 89 , 100 ], it is not without limitations. One such disadvantage is its reliance on the operator, which introduces the potential for differences in the findings.…”
Section: Resultsmentioning
confidence: 99%
“…Similar concepts are signal strength or signal strength index in other devices. Previous studies found that these values affected the measurement of VD and its reliability [1,2,9,[22][23][24]. You et al [9] reported that a lower SVD and DVD were significantly associated with a lower signal strength index, and it was the strongest impact on the measured retinal VD.…”
Section: Discussionmentioning
confidence: 97%